Anthropology of Sart-Kalmaks of Kyrgyzstan - N. Balinova; I. Khomyakova (Oriental Studies, 2018)
The article assesses the data collected by the anthropologists and the geneticists of the N.N. Miklukho-Maklai Institute of Ethnology and Anthropology, and Moscow State University Museum and Research Institute of Anthropology, who performed a complex anthropometric research of a Sart-Kalmak ethnic group during the 2013 expedition. Body measurements of 84 female and 119 male Sart-Kalmak adults, 830 photographic portraits, fill-out recording forms related to racial traits, and 197 blood samples for genetic analyses were obtained for the study. The average anthropometric measurement values do not vary much among the groups studied. This could be due to either the insufficient number of the collected samples, or the fact that there are in fact no significant differences between the Sart-Kalmaks, the Kyrgyz and the mixed-race as to their somatic features and the size of their head and face. Some peculiarities still need to be noted. Male Sart-Kalmak adults are the tallest of all, whereas the Kyrgyz tend to be more corpulent and their body mass index (BMI) is in the overweight range. Females of the mixed origin tend to be the tallest, however having the least weight and the lowest BMI as compared with the other groups. Kyrgyz male adults show more subcutaneous fat deposition, which is not typical for the women. As for the cephalic index it is the highest in both Sart-Kalmak male and female adults. Sart-Kalmaks and mixed-race men tend to have larger zygomatic diameter and a longer face than the Kyrgyz, whereas females have no such features in their face structure. Both the Sart-Kalmak and the mixed-race males show distinctive difference from the Kyrgyz only by the height of the upper lip and the thickness of the lips. Age-related changes of some morphological parameters in Sart-Kalmak men and women show standard dynamics common for many other ethnic groups. The increase in subcutaneous fat deposition with ageing is the main reason for waistline growth, particularly around the abdomen of both men and women. Most women experience an increase in hip circumference, associated with the manifestation of sexual dimorphism. The fact, that women over 50 tend to grow more abdominal fat, is mentioned by many researchers as menopause-related and accompanied by the accumulation of adipose tissue, mainly, in visceral fat depots. The current research presents the preliminary results of the morphological status analysis of the surveyed groups of the Sart-Kalmaks, the Kyrgyz and those of mixed origin. Based on the data obtained in 2014 from the anthropological survey of sub-ethnic groups of the Kalmyks, we will conduct a comparative analysis of their anthropometric indices with those of the Sart-Kalmaks of Kyrgyzstan. The present research highlights the major trends in the current development of this ethnic group.